Land rights and resource conflicts in Nunavut. (2nd October 2019) - Bernauer, Warren
ABSTRACT: The 1993 Nunavut Agreement was intended to help resolve disputes over resource extraction and facilitate responsible development in Nunavut. However, conflicts have persisted. In the Kivalliq region, debates over uranium mining and mining in caribou calving grounds have caused divisions between different representative organizations created by the Nunavut Agreement. Scholars have explained these conflicts with reference to the structures created by the Nunavut Agreement, especially the corporate structure of the territory's Inuit organizations. While this is an important factor driving these conflicts, I argue that the system of land rights created by the Nunavut Agreement, especially the extinguishment of Aboriginal title, is also an important causal factor in these disputes. I begin with an overview of the concept of Aboriginal title and its extinguishment in British-Canadian law. Next, I discuss the Nunavut Agreement's provisions for land rights, especially the exchange of Aboriginal title over a large territory for fee-simple ownership over relatively small parcels of land. This is followed by an examination of the conflicts over uranium mining and mining in calving grounds. I conclude that the provisions of the Nunavut agreement intended to provide 'certainty' for capital investment have in some cases had the opposite effect by fueling ongoing conflicts.